Protective role of melatonin on blood parameters following irradiation in rat - Ozmerdivenli, Recep; Karacabey, Kursat; Gundogdu, Cemal; Sevindi, Tarik (Academic Journals, 2011)
The aim of this study was to determine the preventive role of melatonin on several blood parameters after irradiation exposure in rats. A total of 100 adult Wistar albino rats were divided into five groups. One group was used as control and other groups were treated with 60, 90, 120 and 160 cGy/min of radiation, respectively. A dose of 4 mg/kg of melatonin was administered subcutaneously to 10 rats from each group exposed to different amounts of radiation. Saline was administered to 10 rats from the control group. 20 days after the completion of the 10-day experiment, the rats were sacrificed and blood samples were collected for determination of erythrocytes, leukocytes, hemoglobin, hematocrit and thrombocyte levels. In the group that received 60 cGy-radiation, the number of erythrocytes were similar to the control group, whereas the leukocyte and thrombocyte counts were increased. In the 90 cGy-radiation exposed rats, erythrocytes, hemoglobin and hematocrit values were low as compared to the controls. In the 120 to 160 cGy-radiation treated rats, leukocyte, hemoglobin, hematocrit and thrombocyte numbers were significantly different from the control groups (P<0.01). In the radiation-melatonin administrated rats, no difference was seen in the blood parameters as compared to the control group, except for the thrombocyte numbers. The thrombocyte numbers in all experimental groups were significantly higher than the controls (P<0.05). Melatonin was effective to reverse the deleterious effects of radiation on the blood parameters in rats and this effect was found to be dose-dependent.
Keywords: Melatonin; blood parameters; radiation